2012
DOI: 10.1016/j.jacc.2011.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Optimal Treatment Strategies for In-Stent Restenosis After Drug-Eluting Stent Implantation

Abstract: For lesions of focal DES restenosis, repeat implantation of SES is more effective in reducing late luminal loss and subsequent restenosis rate than cutting balloon angioplasty. For diffuse DES restenosis, implantation of SES or EES is comparably effective in terms of angiographic and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
0
24
2
Order By: Relevance
“…Another reason for the limited success is the presence of feedback loop between mTORC1 and AKT in certain tumor cells. It seems that mTORC1 inhibition by rapalogs fails to suppress a negative feedback loop that results in phosphorylation and activation of AKT [48,[53][54][55]. These limitations have led to the development of the second generation of mTOR inhibitors known as ATP-competitive mTOR kinase inhibitors [55].…”
Section: Clinical Indications Of M-tor I In Nontransplant Patients Anmentioning
confidence: 99%
“…Another reason for the limited success is the presence of feedback loop between mTORC1 and AKT in certain tumor cells. It seems that mTORC1 inhibition by rapalogs fails to suppress a negative feedback loop that results in phosphorylation and activation of AKT [48,[53][54][55]. These limitations have led to the development of the second generation of mTOR inhibitors known as ATP-competitive mTOR kinase inhibitors [55].…”
Section: Clinical Indications Of M-tor I In Nontransplant Patients Anmentioning
confidence: 99%
“…Eight studies [19][20][21][22][23][24][25][26] with 326 TVR over 1718 patient-years follow-up contributed to the network for DES-ISR and compared 5 different treatments ( Figure 7A). As shown in Figure 7B, BA was inferior to all 4 drug-eluting treatments.…”
Section: Drug-eluting Stent Isrmentioning
confidence: 99%
“…Studies with at least 80% angiographic and 90% clinical follow-up were considered at low risk for attrition bias. On the basis of these criteria, the study by Scheller et al 29 and 3 other studies 21,25,30 were not considered low risk for attrition bias for clinical and angiographic end points, respectively. The risk of bias summary of the included studies is shown in Figure IV …”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…Although residual stent struts are reported to cause inflammation around the struts and work as trigger of neoatherosclerosis by histological studies, particular medical treatment for this phenomenon is not realistic right now. Instead, recent investigations focus on the development and improvement of bioresorbable vascular scaffolds [24][25][26][27] which resolve completely. Interventional strategy for ISR is still controversial.…”
Section: Prevention and Management Of Very Late In-stent Restenosismentioning
confidence: 99%
“…Paclitaxel-coated balloon angioplasty is not inferior to paclitaxel-eluting stents for BMS restenosis [29]. In ISR after DES implantation, a couple of studies have been conducted [24,30,31]. It should be determined whether same or the other DES is more beneficial in preventing recurrence of ISR.…”
Section: Prevention and Management Of Very Late In-stent Restenosismentioning
confidence: 99%